Teacher enthusiasm: Dimensionality and context specificity - Kunter, Mareike; Frenzel, Anne; Nagy, Gabriel; Baumert, Jürgen; Pekrun, Reinhard (Contemporary educational psychology, 2011)
► Direct assessment of teachers’ enthusiasm via teacher questionnaire. ► Study combines teacher and student data. ► Two dimensions of teacher enthusiasm can be distinguished: teaching enthusiasm and subject enthusiasm. ► These dimensions differ in their meaning and context specificity. Enthusiasm is considered an important characteristic of effective teachers. However, the conceptualization of the term in the research literature is inconsistent. Whereas most studies use the term “enthusiasm” to describe features of instruction, some have used it to describe a characteristic of teachers. This research seeks to clarify the concept of teacher enthusiasm, examining its dimensionality and context specificity. The study draws on three samples of teachers who were administered questionnaire measures of enthusiasm. In two samples ( N = 205 and 332), it was possible to match teacher data with data on the students taught. In another sample ( N = 113), additional measures of work-related wellbeing were implemented. Confirmatory multigroup factor analyses showed that two dimensions of teacher enthusiasm can be distinguished, namely enthusiasm for teaching and enthusiasm for the subject. These dimensions differed in their meaning and context specificity. Whereas teaching enthusiasm was systematically linked to occupational wellbeing and to classroom variables, subject enthusiasm related only moderately to other measures of occupational wellbeing and was independent of characteristics of the classes taught.